Formulation and antibacterial activity test toothpaste combination of triclosan-extract ethanol of suji leaves (Pleomele angustifolia N.E Brown) - Elya Zulfa; Rima Andriani (Universitas Ahmad Dahlan, 2017)
The suji leaf are generally used by the community as a gargle to remove plaque. Toothpaste is one form of dosage suitable for oral health with triclosan active ingredients, but triklosan is corrosive, resistant to bacteria, and decrease the hormonal system, especially the thyroid hormone. The aim of this research is to know the effect of the addition of variation of the concentration of combination of triclosan-ethanol extracts of suji leaf (T-EESL) on toothpaste preparation to the chemical characteristics, antibacterial activity of Streptococcus mutans. The ethanol extract of 70% of suji leaf was obtained by maceration method, then made toothpaste preparation with variation of T-EESL combination of FI (1:0), FII (0,5:0,5), FIII (0:1). Toothpaste was tested chemical physics characteristics (organoleptic, viscosity, pH, and foam power), antibacterial activity test. The test results are analyzed descriptively. Based on the results of the research obtained it can be concluded that the results of testing the physical physics of chemistry showed the results that all toothpaste formulas meet the physical characteristics of chemical toothpaste. T-EESL toothpaste (0.5:0,5) (FII) has strong antibacterial activity against Streptococcus mutans so it can be used as an alternative to the existing dosage preparation in the market with triclosan active substance.Â Â